A twisted vengeance : a Kate Clifford mystery - Robb, Candace M. (Robb, Candace M. Kate Clifford mystery, 2017)
"As the fourteenth century comes to a close, York seethes on the brink of civil war--and young widow Kate Clifford, struggling to keep her businesses afloat, realizes that her mother is harboring a dangerous secret... 1399. York is preparing for civil war, teeming with knights and their armed retainers summoned for the city's defense. Henry of Lancaster is rumored to have landed on the northeast coast of England, not so far from York, intent on reclaiming his inheritance--an inheritance which his cousin, King Richard, has declared forfeit. With the city unsettled and rife with rumors, Eleanor Clifford's abrupt return to York upon the mysterious death of her husband in Strasbourg is met with suspicion in the city. Her daughter Kate is determined to keep her distance, but it will not be easy--Eleanor has settled next door with the intention of establishing a house of beguines, or poor sisters. When one of the beguines is set upon in the night by an intruder, Kate knows that for the sake of her own reputation and the safety of her young wards she must investigate. From the first, Eleanor is clearly frightened yet maintains a stubborn silence. The brutal murder of one of Eleanor's servants leads Kate to suspect that her mother's troubles have followed her from Strasbourg. Is she secretly involved in the political upheaval? When one of her wards is frightened by a too-curious stranger, Kate is desperate to draw her mother out of her silence before tragedy strikes her own household."--provided by publisher.